Insights into the Electrochemical Reduction Products and Processes in Silica Anodes for Next‐Generation Lithium‐Ion Batteries. Issue 43 (3rd September 2020) - Entwistle, Jake E.; Booth, Samuel G.; Keeble, Dean S.; Ayub, Faisal; Yan, Maximilian; Corr, Serena A.; Cumming, Denis J.; Patwardhan, Siddharth V.
Abstract: The use of silica as a lithium‐ion battery anode material requires a pretreatment step to induce electrochemical activity. The partially reversible electrochemical reduction reaction between silica and lithium has been postulated to produce silicon, which can subsequently reversibly react with lithium, providing stable capacities higher than graphite materials. Up to now, the electrochemical reduction pathway and the nature of the products were unknown, thereby hampering the design, optimization, and wider uptake of silica‐based anodes. Here, the electrochemical reduction pathway is uncovered and, for the first time, elemental silicon is identified as a reduction product. These insights, gleaned from analysis of the current response and capacity increase during reduction, conclusively demonstrated that silica must be reduced to introduce reversible capacity and the highest capacities of 600 mAh g −1 are achieved by using a constant load discharge at elevated temperature. Characterization via total scattering X‐ray pair distribution function analysis reveal the reduction products are amorphous in nature, highlighting the need for local structural methods to uncover vital information often inaccessible by traditional diffraction. These insights contribute toward understanding the electrochemical reduction of silica and can inform the development of pretreatment processes to enable their incorporation into next‐generation lithium‐ion batteries. Abstract : Silica as a sustainable and low‐cost anode for Li‐ion batteries is engineered for its direct use. The pathway for its electrochemical reduction is uncovered, leading to a significant reduction in the pretreatment time from 100s of hours to 13 h. A stable capacity of 635 mAh g −1 is achieved for silica anodes, which is significantly higher than that of graphite.